Training of a creative personality and the problem of intellectual activity of pupils - Mikšytė , G. (Psichologija, 1981)
In this article some important problems of pupils’ intellectual activity, having a direct relationship with the development of creative thought and application of a problematical method in modern school, have been formulated.